2015
DOI: 10.1149/06801.3481ecst
|View full text |Cite
|
Sign up to set email alerts
|

9000 Hours Operation of a 25 Solid Oxide Cells Stack in Steam Electrolysis Mode

Abstract: The operation of 25 solid oxide cells stacks in steam electrolysis mode over 9000 hours is reported. The stack has been operated at current densities of 0.57 and 0.72 A/cm2, using a 50% steam conversion, in the 750-780°C temperature range. Performance degradation rates of 2.30%/ kh are reported, with some non-homogeneity in the stack repeat units behavior observed. Stack repeat units located at the bottom of the stack feature degradation rates below 2%/kh. The possibility to use the operating temperature as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
3
16
0
Order By: Relevance
“…Figure 10 -inspired by Schefold and co-workes [38] -illustrates the importance in decreasing the long-term degradation rate from e.g. around 2 %/kh as reported by Schefold and co-workes [38] and Corre and Brisse [45] to the long-term degradation rate of 0.3-0.4 %/kh reported here for Cell C at similar test conditions. …”
Section: Microstructures Of Soec Long-term Tested At 125 A/cmsupporting
confidence: 69%
See 1 more Smart Citation
“…Figure 10 -inspired by Schefold and co-workes [38] -illustrates the importance in decreasing the long-term degradation rate from e.g. around 2 %/kh as reported by Schefold and co-workes [38] and Corre and Brisse [45] to the long-term degradation rate of 0.3-0.4 %/kh reported here for Cell C at similar test conditions. …”
Section: Microstructures Of Soec Long-term Tested At 125 A/cmsupporting
confidence: 69%
“…fuel cell mode operation) has shown advantageous for the performance of SOC [4,5]; it should be emphasized that at higher electrolysis current densities irreversible degradation phenomena takes place which are not likely to be recoverable by SOFC operation of the SOC [6,7]. Long-term stability needs to be improved even considering promising results such as reported by Tietz, Corre and Hjalmarsson [8][9][10][11] if SOFC systems, and later SOEC systems, are to operate profitable for several years. Recent work has shown that at high current density (high fuel electrode overpotential) the SOEC experiences long-term, roughly linear, irreversible degradation; typically associated with an increase in the ohmic resistance [7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Holzer et al [14] analyzed the effect of humidity for a H 2 O/H 2 mixture in fuel cell mode. The coarsening of Ni enhanced in high humidity conditions would cause a displacement of nickel particles from the triple phase boundary (TPB) to the inner part of the electrode through volatile Ni(OH) 2 . Lastly, this implies a growth of the effective electrolyte thickness and a reduction of electrochemically active TPB, which leads to an inactive Ni-YSZ region [15,16].…”
Section: Fuel Electrode -Cathodementioning
confidence: 99%
“…Degradation phenomena must also be identified, understood and eliminated or reduced. Over the last few years, some reports on solid oxide electrolysis stacks have been published (1)(2)(3)(4)(5)(6)(7)(8)(9). To our knowledge, only a limited number of studies on the detailed post analysis of a stack have been published so far.…”
Section: Introductionmentioning
confidence: 99%